Політична дискурсологія: проблеми й перспективи розвитку - Соколовська, Світлана Володимирівна; Sokolovska, S. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто питання, які розкривають предметну галузь політичної дискурсології як нового наукового напряму. Основну увагу сфокусовано на дослідженні сутності феномену політичного дискурсу, підходів до його інтерпретації з урахуванням інституціональних і неінституціональних форм спілкування. Проаналізовано теоретичні аспекти методології, пов’язані з критичним, дескриптивним і постмодерністським дискурс-аналізом. У межах системи поглядів різних наукових шкіл виділено основні проблеми в дослідженнях сучасної політичної дискурсології і перспективи її розвитку. The article presents the subject-matter of political disсourse analysis as a new branch of linguistics. The main attention is focused on the research aspects concerning the essence and phenomenology of the political disсourse. The paper deals with the definitions based on the differentiation of the institutional and non-institutional speech forms and such approaches to the political discourse interpretation as linguistic, cratologic, and semiotic ones. The latter is presented in many works. According to it political discourse is interpreted as the semiotic and communicative space, in which the building of political reality and the political system signs interaction take place. The theoretical aspects of methodology are also analysed. They are pertinent to the critical, descriptive, and postmodern methods of discourse analysis. Within the framework of the system of different views the dominant scientific challenges and development prospects in the contemporary political disсourse analysis are revealed.
Political Discourse Analysis: Scientific Challenges and Development Prospects
Keywords: політична дискурсологія political; disсourse analysis; політична лінгвістика; political linguistics; політичний дискурс; political disсourse